The Northern Gulf of Mexico During OAE2 and the Relationship Between Water Depth and Black Shale Development. (4th December 2017) - Lowery, Christopher M.; Cunningham, Robert; Barrie, Craig D.; Bralower, Timothy; Snedden, John W.
Abstract: Despite their name, Oceanic Anoxic Events (OAEs) are not periods of uniform anoxia and black shale deposition in ancient oceans. Shelf environments account for the majority of productivity and organic carbon burial in the modern ocean, and this was likely true in the Cretaceous as well. However, it is unlikely that the mechanisms for such an increase were uniform across all shelf environments. Some, like the northwest margin of Africa, were characterized by strong upwelling, but what might drive enhanced productivity on shelves not geographically suited for upwelling? To address this, we use micropaleontology, carbon isotopes, and sedimentology to present the first record of Oceanic Anoxic Event 2 (OAE2) from the northern Gulf of Mexico shelf. Here OAE2 occurred during the deposition of the well‐oxygenated, inner neritic/lower estuarine Lower Tuscaloosa Sandstone. The overlying organic‐rich oxygen‐poor Marine Tuscaloosa Shale is entirely Turonian in age. We trace organic matter enrichment from the Spinks Core into the deepwater Gulf of Mexico, where wireline log calculations and public geochemical data indicate organic enrichment and anoxia throughout the Cenomanian‐Turonian boundary interval. Redox change and organic matter preservation across the Gulf of Mexico shelf were driven by sea level rise prior to the early Turonian highstand, which caused the advection of nutrient‐rich, oxygen‐poor waters onto the shelf. This results in organic matter mass accumulation rates 1–2 orders of magnitude lower than upwelling sites like the NW African margin, but it likely occurred over a much larger geographic area, suggesting that sea level rise was an important component of the overall increase in carbon burial during OAE2. Plain Language Summary: The Cretaceous (145‐66 million years ago, "Ma") was prone to periods with decreased dissolved oxygen ("anoxia") in large parts of the ocean. These oceanic anoxic events (OAEs) were caused by an increase in nutrients in the oceans, which caused plankton (floating unicellular algae) to increase in number ("increased productivity"); after death, rotting plankton used up all the oxygen in the water. These plankton blooms were not evenly distributed, and parts of the ocean, particularly continental shelves, were much more productive than others. We investigate one possible cause for this on shelf environments by studying fossils and sediments from a core and wells on the northern Gulf of Mexico shelf and deep water during the mid‐Cretaceous OAE2, ~94 Ma. We show for the first time that the deepwater Gulf of Mexico was anoxic during OAE2 and that changes in oxygen and productivity on the shelf were driven by sea level rise. As sea level rose, the low‐oxygen, nutrient‐rich deep waters from the middle of the Gulf climbed onto the shelf, spurring a productivity increase. This is a weaker mechanism for driving productivity than the upwelling that characterizes some shelf sites during OAE2, but it is likely an important process on nonupwelling shelf sites. Key Points: Widespread black shale deposition occurs in deepwater Gulf of Mexico before, during, and after Oceanic Anoxic Event 2 (OAE2) Deoxygenation and organic carbon burial on the northern Gulf of Mexico shelf occur after OAE2 and are primarily controlled by sea level rise Advection of a nutrient‐rich water onto the shelf drove organic carbon enrichment; this process was likely a significant contributor to OAE2